Innovative Economics Learning for 21st Century Skills: Inovasi Pembelajaran Ekonomi dan Keterampilan Abad 21 - Rahmona, Fitria; Fermaisuri, Siti; Armiati, Armiati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Rapid technological and economic transformation in the Industrial Revolution 4.0 era requires economics education to move beyond theoretical knowledge toward the development of 21st century skills, including critical thinking, communication, collaboration, creativity, digital literacy, and entrepreneurship. Specific Background: Recent studies show a shift from teacher-centered instruction to student-centered, experiential, and technology-based learning in economics classrooms, incorporating project-based learning, digital simulations, artificial intelligence tools, internships, and collaborative problem solving. Knowledge Gap: However, most prior research focuses on single methods or specific institutional contexts, with limited systematic synthesis integrating diverse innovative approaches, implementation challenges, and institutional readiness. Aims: This study conducts a Systematic Literature Review using the PRISMA framework to synthesize peer-reviewed articles published between 2021 and 2025 on innovation in economics learning methods and their relation to 21st century skills development. Results: Fourteen selected studies reveal five major categories of innovation: technology-based learning, experiential and project-based learning, collaborative and participatory approaches, entrepreneurship-oriented learning, and self-regulated learning, consistently associated with the development of critical thinking, communication, collaboration, creativity, digital literacy, and entrepreneurial competencies. Novelty: This review provides an integrated conceptual mapping of innovative economics learning methods and their pedagogical mechanisms within a unified analytical framework. Implications: The findings highlight the need for alignment among instructional design, institutional support, digital infrastructure, and educator readiness to advance integrated, contextually relevant economics education for contemporary professional demands. Highlights • Identification of five categories of pedagogical innovation across fourteen peer-reviewed studies.• Consistent linkage between active learning approaches and development of 4C competencies.• Emphasis on institutional readiness and digital infrastructure as enabling conditions. Keywords Economics Education; Learning Innovation; 21st Century Skills; Digital Literacy; Systematic Literature Review